Adherence to iron and folic acid supplementation and associated factors among antenatal care attendants in Northwest Ethiopia - Berhanu Abebaw Mekonnen; Yadeta Dessie; Negga Baraki; Abdu Oumer; Mehari Gebru (Intelektual Pustaka Media Utama, 2020)
Iron and folic acid supplementation is the key approach for anemia prevention and control during pregnancy. In Ethiopia only <1% of pregnant mothers ingest the ideal number of tablets. Although, adherence is the most important challenge, literature is dearth and the predictors are undoubtedly recognized. Institution based quantitative cross sectional study design triangulated with qualitative methods was employed among 395 systematically selected pregnant mothers attending antenatal care in Debre Markos town, Ethiopia. Data were collected using interviewer administered structured questionnaire. Data were entered into Epi data and exported to SPSS software. Bivariate and multivariable Logistic regression with the 95% confidence interval was computed. P-value < 0.05 was declared as statistically significant. Eight in-depth interviews were conducted. The data were entered and analyzed using open code software. Adherence rate was 55.5% (95%CI, 50.5%-60.4%). Pregnant mothers who had; history of anemia during current pregnancy [AOR:7.9, 95%CI (4.44-14.01)], primary education (AOR:4.0, 95%CI (1.88-8.54)], secondary education and above (AOR:3.6, 95%CI (1.20-6.94)], good knowledge of iron and folic acid supplementation [AOR:2.1, 95%CI (1.24-3.56)], and early registration for antenatal care (AOR:1.8, 95%CI (1.06-3.11)] were predictors of iron and folic acid supplementation adherence. The rate of adherence was low. Getting medical advice and fear of illness if missed were the primary reasons that enforce mothers to take the tablets. Hence, improving mothers’ knowledge regarding overall aspects of the tablet through better advice, community teaching and the mass media at large, would improve adherence.